Economic problems of creating innovations - Necheporenko, D. A.; Pererva, P. G. (Український державний університет науки і технологій, 2024)
As a result of the study, the main economic problems in the field of innovation were identified: financing; long time cycle for return on investment; market imperfections; lack of compatibility of standards; intellectual property risks; limited access to resources; high implementation costs; resistance to change; inability to adapt.

Внаслідок проведеного дослідження виявлено основні економічні проблеми у сфері інновацій: фінансування; тривалий тимчасовий цикл повернення інвестицій; недосконалість ринку; нестача сумісності стандартів; ризики інтелектуальної власності; обмежений доступ до ресурсів; високі витрати використання; опір змінам; нездатність адаптації.
Економічні проблеми створення інновацій
Keywords: innovation; economic problems; intellectual property; efficiency; enterprises; інновації; економічні проблеми; інтелектуальна власність; ефективність; підприємства